1988
DOI: 10.1002/app.1988.070360409
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction by polymer–polymer mixtures

Abstract: SynopsisAn extensive study on the turbulent drag reduction caused by the various mixtures of polyacrylamide, purified guargum, xanthangum, and their graft copolymers has been conducted at low concentrations and Re = 14,000 using a turbulent flow rheometer. It has been found in most of the cases that the drag reduction caused by mixtures shows a positive deviation from the linearly additive straight line. This effect is more prominent when the drag reduction caused by both the constituents differ appreciably. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The product, BC, is a polymer, and a synergistic effect of drag reduction by BC is expected (22,23). However the main production stage of BC was after the logarithmic growth phase and the effect mentioned above is not primarily important for BC production.…”
Section: Discussionmentioning
confidence: 99%
“…The product, BC, is a polymer, and a synergistic effect of drag reduction by BC is expected (22,23). However the main production stage of BC was after the logarithmic growth phase and the effect mentioned above is not primarily important for BC production.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that flow conditions can affect the degree of deviation from additivity. Malhotra et al (1988) verified DR of PAM/GG, GG/XG, and PAM/ XG binary solutions and concluded that the degree of DR and synergism depend on polymer concentration and flow rate. They also concluded that positive deviation in additivity occurs when both polymers are rigid.…”
Section: Introductionmentioning
confidence: 87%
“…Solutions of polymer blends have been studied in shear and elongational flows mainly to ascertain the effect of the flow on the miscibility of the system. For miscible mixtures, drag reduction experiments in turbulent flows through pipes13, 14 have shown that the mixture has drag reducing capabilities that exceed that of solutions of each of the individual polymers, especially when at least one of the polymers has a semirigid structure. This motivated our previous studies of the flow of solutions of polymer blends through porous media,15 where we found that while PEO solutions exhibit extension thickening when they flow through porous media, hydroxypropyl guar (HPG) solutions were shear thinning at high concentrations.…”
Section: Introductionmentioning
confidence: 99%